Rhinoscleroma pathogenesis: The type K3 capsule of Klebsiella rhinoscleromatis is a virulence factor not involved in Mikulicz cells formation. - Barbara Corelli; Ana S Almeida; Fabiane Sonego; Virginia Castiglia; Cindy Fevre; Sylvain Brisse; Philippe J Sansonetti; Régis Tournebize (Public Library of Science (PLoS), 2018)
Rhinoscleroma is a human specific chronic granulomatous infection of the nose and upper airways caused by the Gram-negative bacterium Klebsiella pneumoniae subsp. rhinoscleromatis. Although considered a rare disease, it is endemic in low-income countries where hygienic conditions are poor. A hallmark of this pathology is the appearance of atypical foamy monocytes called Mikulicz cells. However, the pathogenesis of rhinoscleroma remains poorly investigated. Capsule polysaccharide (CPS) is a prominent virulence factor in bacteria. All K. rhinoscleromatis strains are of K3 serotype, suggesting that CPS can be an important driver of rhinoscleroma disease. In this study, we describe the creation of the first mutant of K. rhinoscleromatis, inactivated in its capsule export machinery. Using a murine model recapitulating the formation of Mikulicz cells in lungs, we observed that a K. rhinoscleromatis CPS mutant (KR cps-) is strongly attenuated and that mice infected with a high dose of KR cps- are still able to induce Mikulicz cells formation, unlike a K. pneumoniae capsule mutant, and to partially recapitulate the characteristic strong production of IL-10. Altogether, the results of this study show that CPS is a virulence factor of K. rhinoscleromatis not involved in the specific appearance of Mikulicz cells.